Development and validation according to the SANTE guidelines of a QuEChERS-UHPLC-QTOF-MS method for the screening of 204 pesticides in bivalves. (30th August 2022) - Diallo, Thierno; Makni, Yassine; Lerebours, Adélaïde; Thomas, Hélène; Guérin, Thierry; Parinet, Julien
Highlights: First qualitative screening of a mix of 204 pesticides in bivalves by UHPLC-QTOF-MS. Taguchi orthogonal array used to simplify the optimisation of the QuEChERS method. IDA-PIL provides better quality and easier to interpret MS/MS spectra than SWATH. Method validation was performed according to SANTE/12682/2019. Screening detection limits were ≤0.05 mg.kg for 81% of pesticides. Abstract: A qualitative screening high resolution mass spectrometry method was developed and validated according to the EU SANTE/12682/2019 guidelines for the analysis of 204 pesticides in seven commercial bivalve species spiked at three concentrations (0.01, 0.05 and, 0.1 mg.kg −1 ). Samples were extracted using QuEChERS and analysed using ultra-high-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry. The QuEChERS method was optimised by the Taguchi Orthogonal Array approach. The best conditions were obtained with pure ACN, MgSO4 /NaCl as extraction salts, MgSO4 /PSA/C18 as clean-up, and the non-dilution of extracts. The impact of different HRMS acquisition modes on detection and identification rates were also evaluated. The screening detection limits were determined to be 0.01 mg.kg −1 and 0.1 for 66% and 87% of pesticides, respectively. These screening procedure was finally applied to different bivalve samples using target and suspect analysis. This allowed the identification of diuron and its metabolite 1-(3, 4-dichlorophenyl)-3-methylurea in the investigated samples.